Fish pathogens near the Arctic Circle: molecular, morphological and ecological evidence for unexpected diversity of Diplostomum (Digenea: Diplostomidae) in Iceland - Blasco-Costa, Isabel; Faltýnková, Anna; Georgieva, Simona; Skírnisson, Karl; Scholz, Tomáš; Kostadinova, Aneta (International journal for parasitology, 2014)
Host-parasite systems at high latitudes are promising model systems for detecting and predicting the impact of accelerated environmental change. A major challenge is the lack of baselines for the diversity and distribution of parasites in Arctic wildlife, especially in the freshwater environment. Here we present the first known estimates of the species diversity and host associations of Diplostomum spp. in sub-Arctic freshwater ecosystems of the Palaearctic. Our analyses integrating different analytical approaches, phylogenies based on mitochondrial and nuclear DNA, estimates of genetic divergence, character-based barcoding, morphological examination, precise detection of microhabitat specialisation and host use, led to the discovery of one described and five putative new species that complete their life-cycles within a fairly narrow geographic area in Iceland. This increases the species richness of Diplostomum in Iceland by 200% and raises the number of molecularly characterised species from the Palaearctic to 17 species. Our results suggest that the diversity of Diplostomum spp. is underestimated globally in the high latitude ecosystems and call for a cautionary approach to pathogen identification in developing the much needed baselines of pathogen diversity that may help detect effects of climate change in the freshwater environment of the sub-Arctic.
Keywords: Animals; Ecosystem; Fish Diseases; Arctic Regions; genetická variace; ryby; Genetic Variation; biodiverzita; Sub-Arctic; fylogeneze; cox1; Diplostomum; ITS; Phylogeny; Fish pathogens; ekosystém; Iceland; zvířata; Trematoda; DNA helmintů; Integrative taxonomy; Arktida; nemoci ryb; Trematode Infections; Island; DNA, Helminth; Biodiversity; infekce červy třídy Trematoda; Fishes